BMP signaling modulates hepcidin expression in zebrafish embryos independent of hemojuvelin. - Yann Gibert; Victoria J Lattanzi; Aileen W Zhen; Lea Vedder; Frédéric Brunet; Sarah A Faasse; Jodie L Babitt; Herbert Y Lin; Matthias Hammerschmidt; Paula G Fraenkel (PLoS ONE)
Hemojuvelin (Hjv), a member of the repulsive-guidance molecule (RGM) family, upregulates transcription of the iron regulatory hormone hepcidin by activating the bone morphogenetic protein (BMP) signaling pathway in mammalian cells. Mammalian models have identified furin, neogenin, and matriptase-2 as modifiers of Hjv's function. Using the zebrafish model, we evaluated the effects of hjv and its interacting proteins on hepcidin expression during embryonic development. We found that hjv is strongly expressed in the notochord and somites of the zebrafish embryo and that morpholino knockdown of hjv impaired the development of these structures. Knockdown of hjv or other hjv-related genes, including zebrafish orthologs of furin or neogenin, however, failed to decrease hepcidin expression relative to liver size. In contrast, overexpression of bmp2b or knockdown of matriptase-2 enhanced the intensity and extent of hepcidin expression in zebrafish embryos, but this occurred in an hjv-independent manner. Furthermore, we demonstrated that zebrafish hjv can activate the human hepcidin promoter and enhance BMP responsive gene expression in vitro, but is expressed at low levels in the zebrafish embryonic liver. Taken together, these data support an alternative mechanism for hepcidin regulation during zebrafish embryonic development, which is independent of hjv.